Terahertz oscillations in mercury cuprate superconductors - (:unkn) unknown (INDIAN ACAD SCIENCES, 2009)
It has been recently reported that the three-dimensional Bose-Einstein condensation of the quasi-particles is valid for the mercury cuprates at liquid helium temperature. In this study, the validity of the interlayer theory in three dimensions has been investigated for optimally oxygen-doped mercury cuprates at the temperature interval of 0-15 K. Furthermore, some thermodynamic and electrodynamics parameters of mercury cuprates have been calculated for both the under-doped and the over-doped samples at the vicinity of 4.2 K. Moreover, it has been determined that the superconducting system behaves as a terahertz wave cavity regardless of the oxygen doping concentration.
Keywords: Mercury cuprates; terahertz oscillations; interlayer theory; Bose-Einstein condensation; BOSE-EINSTEIN CONDENSATION; C-AXIS ELECTRODYNAMICS; POLARITONS; PARAMETERS; EXCITONS; PLASMA